Panniculitis, A Rare Presentation of Onset and Exacerbation of Juvenile Dermatomyositis: A Case Report and Literature Review - Yun Jung CHOI; Wan-hee YOO (Archives of Rheumatology, 2018)
Panniculitis occurring in juvenile dermatomyositis has been rarely reported. However, it may lead to poor quality of life, and furthermore, induce an irreversible structural change in the subcutaneous layer. In this article, we present the case of a 10-year-old female patient with panniculitis that simultaneously developed with the onset and flare-up of juvenile dermatomyositis. In addition, a brief literature review of cases regarding juvenile dermatomyositis-associated panniculitis emphasizes the importance of recognizing panniculitis as a cutaneous manifestation of juvenile dermatomyositis.